Kinetics and Thermodynamics Studies of Ketalization of Glycerol and Acetone in the Presence of Basolite F300 as Catalyst. Issue 1 (January 2020) - Sulistyo, Hary; Perdana, Indra; Pratiwi, Fatimah Tresna; Hartati, Indah
Abstract: Acetalyzation of glycerol with acetone has been carried out using Basolite F300 as catalyst. Heterogeneous catalysis reaction model was employed and Langmuir Hinshelwood mechanism was simulated and validated to the experimental data. The experiment was conducted at varying temperature (30 – 55°C) with an initial molar ratio of glycerol to acetone of 1:4, agitation speed of 700 rpm and catalyst loading of 1% (w/w glycerol). The agitation speed of 700 rpm was sufficient to neglect the external mass transfer as the rate controlling step.The results showed that glycerol conversion as high as 83.33 % was obtained from one hour reaction time. The glycerol conversion was simulated and the results were compared with experimental data in a temperature range of 30°C to 55°C. From mathematical model, it was found that the pre-exponential factor of 0.0149 min –1 and activation energy of 15.7085 kJ.mole –1 . Comparison of experimental data and calculation results showed that the proposed mathematical model was adequately able to approach the experimental data within the temperature range under investigation. Thermodynamics analysis on the ketalization resulted in Δ S °, Δ H ° and Δ G ° which values were 0.0834 kJ.mole –1 K –1, -29.7176 kJ.mole –1 and -4.8675 kJ.mole –1, respectively.